CIGR handbook of agricultural engineering (ASAE, 1999)
This handbook is designed to cover the major fields of agricultural engineering such as soil and water, machinery and its management,farm structures and processing agricultural, as well as other emerging fields. information on technology for rural planning and farming systems, aquaculture, environmental technology for plant and animal production, energy and biomass engineering is also incorporated in this handbook.